INNOVATIONS AND TOURISTIC ACTIVITY EVOLUTION - V. S. Novikov (Модернизация, инновация, развитие, 2016)
Fundamental and applied innovations impact activities in the tourist industry and evolution thereof. More and more sophisticated technologies and communication techniques are practically used to serve tourists. Basically, innovative tourist activity development concept represents innovation of values and in particular means that tourist’s impression is taken into account to higher extent and tourist product personification changes the products’ consumer value. Discussed in the article are tourist activity, tourist cluster, destination and glocalization development prospects.